The Influence Of Dynamic Capabilities, Competencies, Motivation, And Information Technology On Innovation Performance For Nursing - Saryadi Saryadi; Liss Dyah Dewi Arini (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2023)
This study aims to determine the influence of dynamic capabilities, competencies, motivation, and information technology on innovation performance. The research was conducted at RSST Klaten with the object of nursing staff filling out the gform. The population is 410 people with a sample of 41 respondents or 10%. This is due to various problems such as limited ability of researchers, time and costs in researchers by means of accidental random sampling. The results showed a significant positive influence of dynamic capability variables on innovation performance Competency had a positive but not significant effect on innovation performance. Motivation has a negative and insignificant effect on the performance of Information Technology innovation has a negative and insignificant effect on innovation performance. The results of the F test show that all independent variables have a significant influence on innovation performance. R2 value of 0.359 means that innovation performance is explained by Dynamic Capability, Competence and Motivation, and Information Technology by 35.9% and the remaining 64.1% is explained by other variables outside the research model, such as compensation variables, work discipline and others